Chemical technology of oligomers production from homopolymer based on epichlorohydrin and morpholine - Urinov Ulugbek; Hamidova Nilufar; Mirzakulov Ilhom (E3S Web of Conferences, 2024)
In this paper, the effect of different solvents on the spontaneous polymerization reaction of morpholine and epichlorohydrin is studied. Also. The reaction have been established: factors temperature, proportions of initial substances, optimal values of such parameters as temperature.On the basis of the developed technology the yield of oligomeric product with epichlorohydrin based on morpholine 92-95% was determined. The structure of the synthesized oligomeric substance was established by spectral methods, IR, PMR spectroscopy.The technological scheme for the preparation of polymer products based on 3-chloro-1-morpholyl-2-isopropylacrylate was also developed and the influence of reaction time, temperature and ratio of initial substances on the process was studied. Preparation of oligomer based on morpholine with epichlorohydrin.Processes and technology for obtaining homopolymers based on 3-chloro-1-morpholyl-2-isopropylacrylate were developed.